Attitudes, Influences and Perceptions towards Plastic Surgery amongst Medical Students. (September 2021) - Kidd, Thomas; Palaniappan, Subbramanian; Kidd, Daniel; Waterston, Stuart
Abstract: Introduction: Plastic surgery is a dynamic and evolving field but remains poorly understood due to lack of knowledge, media misconceptions and recent changes to medical undergraduate curricula. To address issues around student interest and recruitment into the speciality, it is imperative to understand the factors influencing medical students and future clinicians. Aims: To examine influences, interest and perceptions of plastic surgery amongst Scottish medical students and explore methods to increase undergraduate engagement. Method: Cross-sectional survey distributed online via Scottish undergraduate medical school offices comprising 6 domains: demographics; career interest; perceptions, interests and influences in plastic surgery; curriculum and trainer views; understanding the role of a plastic surgeon; and undergraduate engagement. Results: A total of 193 students responded with no statistically significant relationship between year group, gender, and interest in plastic surgery. Phrases most strongly identified with plastic surgery included private practice, reconstruction and cosmetics. Placements, teaching staff and workshops/courses were found to influence perception of plastic surgery. Fortunately, only 6% of students encountered antagonism towards plastic surgery encompassing themes of negative stereotypes of surgeons and connotations surrounding cosmetic surgery. Importantly, many students were largely unaware of the range of common procedures undertaken by plastic surgeons. To overcome this lack of awareness and generate greater interest, students suggested greater plastics exposure, consultant-led teaching and workshops showcasing the specialty. Conclusion: Medical students want varied, stimulating and flexible careers – something which plastic surgery can provide. However it seems the understanding of the scope of plastic surgery is poorly understood amongs future trainees. To increase uptake and interest, negative perceptions need to be addressed and greater engagement is required from medical school upwards.